2015
DOI: 10.1016/j.jclepro.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable–smart–resilient–low carbon–eco–knowledge cities; making sense of a multitude of concepts promoting sustainable urbanization

Abstract: Over the last couple of decades, metropolitan areas around the world have been engaged in a multitude of initiatives aimed at upgrading urban infrastructure and services, with a view to creating better environmental, social and economic conditions and enhancing cities' attractiveness and competitiveness. Reflecting these developments, many new categories of 'cities' have entered the policy discourse:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
471
0
42

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 821 publications
(520 citation statements)
references
References 55 publications
7
471
0
42
Order By: Relevance
“…A recent study (De Jong et al, 2015) highlighted twelve different categories of cities in the literature for the period running from 1996 to 2013: 'sustainable city', 'eco city', 'low carbon city', 'liveable city', 'green city', 'smart city', 'digital city', ubiquitous city', intelligent city', 'information city', 'knowledge city', and 'resilient city'. They found 'sustainable city' had the highest number of occurrences followed by 'smart city'.…”
Section: Reflectionsmentioning
confidence: 99%
“…A recent study (De Jong et al, 2015) highlighted twelve different categories of cities in the literature for the period running from 1996 to 2013: 'sustainable city', 'eco city', 'low carbon city', 'liveable city', 'green city', 'smart city', 'digital city', ubiquitous city', intelligent city', 'information city', 'knowledge city', and 'resilient city'. They found 'sustainable city' had the highest number of occurrences followed by 'smart city'.…”
Section: Reflectionsmentioning
confidence: 99%
“…Literature reviews [5] revealed a multitude of terms relating to upgrading of urban infrastructure and services used by policy makers, planners, developers and in academic literatures. Twelve distinct city categories were identified in academic literatures between the period 1996 -2013, these were: 'eco city', 'sustainable city', 'smart city', 'low carbon city', 'knowledge city', 'intelligent city', 'digital city', 'ubiquitous city', 'resilient city', 'green city', 'information city', and 'liveable city'.…”
Section: Smart City Definitionmentioning
confidence: 99%
“…Work by Joss and Molella [22] and more recently by de Jong et al [23] sheds light on the rise in eco-city initiatives and the related increase in the number of categories which have entered the policy discourse as a result. While sustainable city initiatives generally aim to improve the environmental, economic and social conditions of the city and those living in it, they are variously framed according to a diverse and growing list of categories, including for example "eco cities", "liveable cities", "green cities", and "smart cities", among others [23].…”
Section: Origins Of Contemporary Ecourbanismmentioning
confidence: 99%
“…While sustainable city initiatives generally aim to improve the environmental, economic and social conditions of the city and those living in it, they are variously framed according to a diverse and growing list of categories, including for example "eco cities", "liveable cities", "green cities", and "smart cities", among others [23]. This diversity demonstrates the wide array of motivations and goals for which sustainable cities are being planned and developed, and also the overlapping nature and "co-dependence of environmental, economic and social dimensions" of sustainable development at the city scale [23] (p. 2). Yu [24] notes that the concepts of eco-city, low carbon city and low carbon ecocity are increasingly guiding government responses, both central and local, in China.…”
Section: Origins Of Contemporary Ecourbanismmentioning
confidence: 99%